2009
DOI: 10.1289/ehp.11627
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Endocrine Disruption in Southern California Coastal Fish Using an Aquatic Multispecies Microarray

Abstract: BackgroundEndocrine disruptors include plasticizers, pesticides, detergents, and pharmaceuticals. Turbot and other flatfish are used to characterize the presence of chemicals in the marine environment. Unfortunately, there are relatively few genes of turbot and other flatfish in GenBank, which limits the use of molecular tools such as microarrays and quantitative reverse-transcriptase polymerase chain reaction (qRT-PCR) to study disruption of endocrine responses in sentinel fish captured by regulatory agencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 55 publications
(55 reference statements)
2
64
0
Order By: Relevance
“…Data are presented as a heat map of relative over- and under-expression in rosiglitazone treated with respect to control DMSO treated NRVMs (Figure 6). Q-PCR was carried out as described previously [36]. This revealed that these transcripts were progressively upregulated as the time course proceeded and validated the array data.…”
Section: Resultsmentioning
confidence: 72%
“…Data are presented as a heat map of relative over- and under-expression in rosiglitazone treated with respect to control DMSO treated NRVMs (Figure 6). Q-PCR was carried out as described previously [36]. This revealed that these transcripts were progressively upregulated as the time course proceeded and validated the array data.…”
Section: Resultsmentioning
confidence: 72%
“…For example, molecular biomarkers such as thyroid hormone levels or gene expression (Baker et al 2009;Brar et al 2010), when coupled with histological assays of body condition, can reveal the energetic consequences of suppressed thyroid function and tumor growth in wild-caught organisms. Field studies are important in determining how energetic responses to contaminants are mediated by diel temperature variability, seasonal hydrology, resource availability, and predator-prey relationships (Clark and Clements 2006;Buchwalter et al 2007).…”
Section: Emerging Research Approachesmentioning
confidence: 99%
“…Thus, when comparing a highly PAH-contaminated environment with a 'clean' reference site, flounder transcripts characteristic of acute PAH-response were changed (Williams et al, 2003). Similarly, when comparing hornyhead turbot (Pleuronichthys verticalis) from a site receiving an estrogenic effluent with a clean site, a signal characteristic of acute estrogen exposure was observed (Baker et al, 2009). However, in a larger study, involving several European estuaries of differing pollutant status, and using a more comprehensive microarray, a transcriptomic signal of pollutant effect was less clear (Falciani et al, 2008).…”
Section: Introductionmentioning
confidence: 99%